(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
In the context of martial law, Ukraine’s agricultural sector is suffering significant losses. By May 2022. Ukraine has already lost almost 13 million tonnes of elevator capacity, some of the grain warehouses have been completely destroyed, and some are in the occupied territories. In this regard, there is a need for elevator capacities, namely, prefabricated, cost-efficient storage capacities. Such structures are exemplified by silos. There are many design solutions for metal silos. However, the rising cost of materials is causing a need to reduce the material intensity of the structure, which is encouraging cylindrical silo manufacturers to search for new types of shell construction. An innovative design of lightweight, industrial silos is a metal spiral-fold silo. The article describes the design of steel spiral-fold silos. The specifics of the spiral-fold silo design, which affects their stress-strain state, are analysed. The characteristics of the silo that was used as a source of samples for the experiment are given. The samples and equipment for the experimental study of a wall of a metal spiral-fold silo are considered. The stages of the experiment are described. The loading of the samples was performed by a central bending load applied in a static mode in the range from 0 kN to 5.5 kN. To determine the relative strains, the structure was unloaded after each loading stage. The analysis of the sample’s relative strains which were measured by AVD-4 is made. The character of interaction and deformation of the wall with the folding lock is revealed. The degree of the folding lock opening was estimated. The character of work of the wall and the folding lock in the limit and non-limit states is obtained. A comparison of experimental results with finite element analysis in the LIRA-SAPR software package was performed. The conclusion about the reliable operation of the wall of a spiral- fold silo under operational and increased loads is substantiated.